A head-to-head comparison of fast-SENC and feature tracking to LV long axis strain for assessment of myocardial deformation in chest pain patients - Siry, Deborah; Riffel, Johannes; Salatzki, Janek; André, Florian; Weberling, Lukas D.; Ochs, Marco; Atia, Noura Abdelmonem Nooman; Hillier, Elizabeth; Albert, David; Katus, Hugo; Giannitsis, Evangelos; Frey, Norbert; et al. (BMC medical imaging, 2022)
Myocardial strain imaging has gained importance in cardiac magnetic resonance (CMR) imaging in recent years as an even more sensitive marker of early left ventricular dysfunction than left-ventricular ejection fraction (LVEF). fSENC (fast strain encoded imaging) and FT (feature tracking) both allow for reproducible assessment of myocardial strain. However, left-ventricular long axis strain (LVLAS) might enable an equally sensitive measurement of myocardial deformation as global longitudinal or circumferential strain in a more rapid and simple fashion.